Faktor Determinan Maternal Terhadap Kejadian Stunting Pada Balita Usia 2–5 Tahun Di Kabupaten Kediri - Nurcahyanti, Febrina Dwi; Astuti, Trihaningsih Puji (Yayasan Jompa Research and Development, 2025)
This study aimed to identify maternal factors associated with stunting among children aged 2 to 5 years in Kediri Regency. The study used an analytical observational design with a case–control approach involving a population of 145 children and a sample of 106 respondents selected through purposive sampling. The research variables included maternal education, family income, childcare practices, maternal nutritional status during pregnancy, and low birth weight (LBW). Data were collected using questionnaires and medical record review, and analyzed through univariate analysis, Chi-square tests for bivariate analysis, and logistic regression for multivariate modelling. The results showed that childcare practices, maternal education, LBW, and maternal nutritional status during pregnancy were significantly associated with stunting in the bivariate analysis. However, only LBW remained a significant determinant in the multivariate model, with children who had a history of LBW being 8.56 times more likely to experience stunting than those with normal birth weight. This study concludes that LBW is the dominant maternal-related factor influencing stunting among children in Kediri Regency. Strengthening maternal nutrition, improving the quality of antenatal care, and ensuring optimal management of LBW infants are essential strategies to reduce the risk of stunting. Keywords: Child, Low Birth Weight, Maternal Factors, Stunting